2021 13th International Conference on Quality of Multimedia Experience (QoMEX) 2021
DOI: 10.1109/qomex51781.2021.9465445
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation of Objective Image Quality Metrics on Conventional and Learning-Based Compression Artifacts

Abstract: Lossy image compression is a popular, simple and effective solution to reduce the amount of data representing digital pictures. In most lossy compression methods, the reduced volume of data in bits is achieved at the expense of introducing visual artifacts in the picture. The perceptual quality impact of such artifacts can be assessed with expensive and timeconsuming subjective image quality experiments or through objective image quality metrics. However, the faster and less resource demanding objective qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 16 publications
1
18
0
Order By: Relevance
“…On the other hand, the levels of performance attained by the PSNR family, which are commonly used in compression, were poor. Like other studies in the literature that analysed the perceptual quality of learning based image compression models [68], [69], our experiments also confirmed the value and perceptual relevance using models like MS-SSIM, VIF, and VMAF.…”
Section: E Subjective Study and Analysissupporting
confidence: 87%
See 1 more Smart Citation
“…On the other hand, the levels of performance attained by the PSNR family, which are commonly used in compression, were poor. Like other studies in the literature that analysed the perceptual quality of learning based image compression models [68], [69], our experiments also confirmed the value and perceptual relevance using models like MS-SSIM, VIF, and VMAF.…”
Section: E Subjective Study and Analysissupporting
confidence: 87%
“…Aside from measuring the pixel-wise PSNR for completeness, we mainly relied on perception-based quality models, including MS-SSIM [65], VIF [66] and VMAF [67], to quantify the distortion levels that were used for BD-rate calculation. We are aware of recent studies [68], [69] of quality evaluation on deep learning based image compression. It has been shown that in this context, these three perceptual quality models have the highest correlation against subjective scores, whereas absolute fidelity models like the PSNR correlate poorly with visual perception, producing significantly inferior quality predictions than perception-based quality predictors.…”
Section: A Evaluation Experimentsmentioning
confidence: 99%
“…It has been concluded that conventional PSNR and SSIM metrics are not appropriate to assess the quality of deep learning-based compressed images. A similar work using 8 reference images and focusing on traditional objective quality assessment metrics has also been presented in [52].…”
Section: Related Workmentioning
confidence: 99%
“…The distorted images, obtained with the standard JPEG2000 coding standard and some recent neural networks based compression algorithms, as well as their associated MOS are made publicly available. Moreover, compared to the previous subjective studies [52,55], the proposed database includes more reference images with recent NN compression algorithms resulting in a larger dataset. It is worth pointing out that such new subjective dataset presents a great interest to the research communities working both on the development of IQA algorithms as well as the design of deep learning based compression algorithms.…”
Section: Limitations and Contributionsmentioning
confidence: 99%
See 1 more Smart Citation